Study of crystallization, microstructure and mechanical properties of lithium disilicate glass-ceramics as a function of the sintering temperature - Campanelli de Morais, Dayana; Ferreira Theotonio Santos, Matheus; Moreira Bastos Campos, Tiago; de Sousa Trichês, Eliandra; Souto Borges, Alexandre Luiz (Brazilian Dental Science, 2021)
Objective: The purpose of the present study was to synthesize and characterize lithium disilicate glass-ceramics through the Li2 O-SiO2 system for determining the most satisfactory sintering parameter by evaluating the crystalline composition, microstructure and mechanical properties. Material and methods: The glass-ceramics were prepared from a glass precursor by means of the melting/cooling technique with a composition of 33.33 Li2 O and 66.67 SiO2 (mol.%). The specimens were compressed by the uniaxial pressing technique and three different thermal treatments were used for sintering: 850 °C (Group 1), 900 °C (Group 2), and 950 °C (Group 3), which were determined based on the differential scanning calorimetry (DSC) result. The glass-ceramics were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), Archimedes method, microhardness and biaxial flexural strength analyses. Results: The results regarding XRD predominantly showed lithium disilicate phase for all the heat treatments performed. Moreover, grains with a needle form were more predominantly observed in the SEM images for Group 3, as well as a higher densification and consequently higher mechanical properties. In contrast, Group 1 presented the lowest mechanical properties and densification, as well as the highest porosity. Conclusion: The present study demonstrated how extremely important it is to follow the heat treatment recommended by the manufacturers of ceramics, including time and temperature, which possess direct effects in the crystalline phase formation, as well as in the material’s microstructure and mechanical properties. KeywordsCrystallization; Glass-ceramics; Lithium disilicate.